Diagnóstico socioambiental da bacia hidrográfica do Rio Calabouço-PB/RN - Silva, Rafael Fernandes da (2011)
This paper presents the socioenvironmental diagnosis of watershed from river Calabouço PB/RN, with emphasis on environmental issues. Aimed to conduct an analysis of geoenvironmental conditions (geology, geomorphology, climate and hydrology, soils and biodiversity). The theorical framework is made up of issues relating to the availability and access to water, the watershed concept as the basic unit for environmental planning and development and sustainability. The methodology is structured en two parts, the first conceptual refers to the approach General Theory of Systems applied in environmental studies. The second part dealt with the technical procedures of this research, which included the use of characterization form of the physical environment, and System Image Processing Georeferenced (SPRING). The watershed from river Calabouço (BHRC) PB/ RN, is located between coordinates of 6° 24 53 and 6° 39 49 S, 35° 26 16 and 35° 49 49 W, has an area of approximately 688 km², an area of intersection between the Wasteland region of Paraíba and Rio Grande do Norte Potiguar Wasteland. The geological structure of the BHRC is marked by three sets: the Cenozoic formations represents 6% of the Neoproterozoic formations is 18,5% and Paleoproterozoic formations, represented by the complex Santa Cruz with a percentage of 53,7% and complex Serrinha-Pedro Velho with only 22%. The geomorphology consists of mountains of a horst Araruna and Confusion in contrast to the depression of the Graben Curimatatú, corresponding to a cavity resulting from tectonic faults, with average elevation of 300 meters, and unevenness of 300 meters between the low and highest tops of the mountains nearby. The watershed present climate of transition, As tropical hot and humid, with hot summers and rainy and cold and dry winter and dry season up to six months, rainfall averages between 800mm and 1500mm, and Bsh semi-humid climate, average rainfall between 500mm to 800mm annually. The interaction between climate and geology provided the BHRC the disposition of a dendritic drainage pattern, as studies of watersheds by CHRISTOFOLETTI (1986). The fluvial hierarchy BHRC presents an area drained by rivers of 1st, 2nd, 3rd and 4th orders, and the 1st order consists of 55 channels, the 2nd order of 22 channels, the 3rd order of for 8 channels and 4th order for only one channel, which consists of the ara drained by the main river, the Calabouço River. The results find that the BHRC is gratly affected Throughout its lengtg by anthropic impacts on areas that should be preserved, which are occupied by activities such as agriculture, livestock, tourism and urban development. From these elements is observed in several cases, the lack of efficiency in implementing the National Policy of Water Resources, hence the need to establish a discussion around the options exercised by society and its impact on construction and spatial integration of BHRC PB/RN.